Facing the Normative Challenges: The Potential of Reflexive Historical Research - Stutz, Christian; Sachs, Sybille (Business & society, 2018)
This article explores methodological problems of qualitative research templates, that is, the Eisenhardt and the Gioia case study approaches, which are relevant for the business and society (B&S) scholarship and outlines a reflexive historical research methodology that has the potential to face these challenges. Building on Hans-Georg Gadamer’s philosophical hermeneutics, we draw critical attention to qualitative B&S research and frame the methodological problems identified as the normative challenges of qualitative research, that is, to productively deal with both the researchers’ norms and the research subjects’ norms. We then introduce the reflexive historical case study (RHCS), a distinct research strategy to face normative challenges based on philosophical hermeneutics and the interpretive tradition of studying organizations. This research approach aims at theory elaboration while its mode of enquiry is reflexive. By explicating three of its key characteristics and using a case example to illustrate our approach, we demonstrate how B&S scholars can benefit from the “temporal filter” of the historical lens and from reflexive concerns about the nature of theory and empirical material. To tap the potential of historical research, we finally envision a research program for studying issues and debates associated with B&S scholarship.